Internet censorship detected in Morocco (Morocco) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Morocco. Data sourced from CensoredPlanet.
Censorship Incident ID: MA-2026-0217. Severity: critical. Confidence: 65%